Phytoplankton response to polystyrene microplastics: Perspective from an entire growth period - Mao, Yufeng; Ai, Hainan; Chen, Yi; Zhang, Zhenyu; Zeng, Peng; Kang, Li; Li, Wei; Gu, Weikang; He, Qiang; Li, Hong (Chemosphere (Oxford), 2018)
Microplastics are widely identified in aquatic environments, but their impacts on phytoplankton have not been extensively studied. Here, the responses of Chlorella pyrenoidosa under polystyrene (PS) microplastics exposure were studied across its whole growth period, with microplastic sizes of 0.1 and 1.0 μm and 3 concentration gradients each, which covered (10 and 50 mg/L) and exceeded (100 mg/L) its environmental concentrations, respectively. PS microplastics caused dose-dependent adverse effects on Chlorella pyrenoidosa growth from the lag to the earlier logarithmic phases, but exhibited slight difference in the maximal inhibition ratio (approximately 38%) with respect to the two microplastic sizes. In addition to the reduced photosynthetic activity of Chlorella pyrenoidosa, unclear pyrenoids, distorted thylakoids and damaged cell membrane were observed, attributing to the physical damage and oxidative stress caused by microplastics. However, from the end of the logarithmic to the stationary phase, Chlorella pyrenoidosa could reduce the adverse effects of microplastics jointly through cell wall thickening, algae homo-aggregation and algae-microplastics hetero-aggregation, hence triggering an increase of algal photosynthetic activity and its growth, and cell structures turned to normal. Our study confirmed that PS microplastics can impair but then enhance algae growth, which will be helpful in understanding the ecological risks of microplastics. [Display omitted] •Effects of PS microplastics on algae were studied over its entire growth period.•PS microplastics caused depression but then stimulation of algal growth.•Physical damage and oxidative stress are involved in depression of algal growth.